The impact of street properties on cognitive maps - Mohsenin, Mahsan; Sevtsuk, Andres (Journal of Architecture and Urbanism, 2013)
This paper investigates the relationship between street properties and cognitive maps. It is focused on the question of how human cognition of the built environment is affected by street properties. Building on the foundations of Kevin Lynch’s studies of environmental perception (Lynch 1960) and recent configuration measurement techniques of the built environment, it addresses an important question that Lynch has left unresolved: Why do people have more complete recollections of some parts of the urban environment, and not others? This paper proposes an analytical measurement framework based on graph theory to compare the results of cognitive maps with objective spatial properties of the corresponding built environment. In order to test our hypothesis, street geometry is measured and defined based on graph theory in two selected areas with similar geometries in Kenmore, Boston and Kendall Sq., Cambridge, MA. Cognitive maps are then collected based on specifically designed map drawing surveys. Finally, the relationship between graph results and cognitive maps is examined in order to identify the ways that street properties affect human perception.